2002
DOI: 10.1073/pnas.122254599
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lkb1 , the causative gene of Peutz–Jegher's syndrome, in embryogenesis and polyposis

Abstract: Peutz-Jeghers syndrome (PJS) is a dominantly inherited human disorder characterized by gastrointestinal hamartomatous polyposis and mucocutaneous melanin pigmentation. LKB1 (STK11) serine͞threonine kinase is the product of the causative gene of PJS, which has been mapped to chromosome 19p13.3. However, several studies have produced results that are not consistent with a link between LKB1 gene mutation and PJS. We constructed a knockout gene mutation of Lkb1 to determine whether it is the causative gene of PJS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
98
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(108 citation statements)
references
References 27 publications
9
98
0
1
Order By: Relevance
“…Homozygous deletion of STK11/LKB1 in mice leads to embryonic lethality at midgestation (E11.0), indicating that STK11/LKB1 plays an important role in embryogenesis (Ylikorkala et al, 2001;Jishage et al, 2002). Interestingly, most of the STK11/LKB1 þ /À mice developed intestinal polyps by the age of 45 weeks, identical to those observed in patients with PJS (Bardeesy et al, 2002;Jishage et al, 2002;Nakau et al, 2002). These results suggested that haploinsufficiency in the STK11/ LKB1 þ /À animals is sufficient to induce polyposis as in humans (Su et al, 1999;Rossi et al, 2002).…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Homozygous deletion of STK11/LKB1 in mice leads to embryonic lethality at midgestation (E11.0), indicating that STK11/LKB1 plays an important role in embryogenesis (Ylikorkala et al, 2001;Jishage et al, 2002). Interestingly, most of the STK11/LKB1 þ /À mice developed intestinal polyps by the age of 45 weeks, identical to those observed in patients with PJS (Bardeesy et al, 2002;Jishage et al, 2002;Nakau et al, 2002). These results suggested that haploinsufficiency in the STK11/ LKB1 þ /À animals is sufficient to induce polyposis as in humans (Su et al, 1999;Rossi et al, 2002).…”
mentioning
confidence: 60%
“…The Stk11/Lkb1 protein is ubiquitously expressed in all human fetal and adult tissues (Rowan et al, 2000). Homozygous deletion of STK11/LKB1 in mice leads to embryonic lethality at midgestation (E11.0), indicating that STK11/LKB1 plays an important role in embryogenesis (Ylikorkala et al, 2001;Jishage et al, 2002). Interestingly, most of the STK11/LKB1 þ /À mice developed intestinal polyps by the age of 45 weeks, identical to those observed in patients with PJS (Bardeesy et al, 2002;Jishage et al, 2002;Nakau et al, 2002).…”
mentioning
confidence: 80%
“…Heterozygous mice are viable but develop hamartomatous polyps, characteristic of PJS, with high penetrance (Bardeesy et al, 2002;Jishage et al, 2002;Miyoshi et al, 2002;Rossi et al, 2002).…”
Section: Peutz-jeghers Syndrome and Human Cancer Geneticsmentioning
confidence: 99%
“…Jansen et al (2006) provide a complete discussion on this point as well as an explanation for the occasional findings of carcinomatous changes within haramartomatous polyps. Furthermore, hamartomas display variable LOH of LKB1 as opposed to carcinomas in PJS patients where LOH is more frequently observed (Wang et al, 1999;Miyaki et al, 2000;Entius et al, 2001;Bardeesy et al, 2002;Jishage et al, 2002;Miyoshi et al, 2002;Rossi et al, 2002;De Leng et al, 2003). Most intriguingly, studies in genetically engineered mouse models have called into question whether the hamartomas arise because of cell autonomous processes (a cell autonomous process involves only genotypically mutant cells exhibiting a mutant phenotype; a non-cell autonomous process involves a genotypically mutant cell causing a mutant phenotype in another cell).…”
Section: Benign and Malignant Tumorigenesismentioning
confidence: 99%
See 1 more Smart Citation